2003
DOI: 10.1016/s0195-668x(03)00237-9
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunity and nonimmunologic risk factors in cardiac allograft vasculopathy

Abstract: Graft vasculopathy is an accelerated form of coronary artery disease that occurs in transplanted hearts. Despite major advances in immunosuppression, the prevalence of the disease has remained substantially unchanged during the last two decades. According to the 'response to injury' paradigm, graft vasculopathy is the result of a continuous inflammatory response to tissue injury initiated by both alloantigen-dependent and independent stress responses. Experimental evidence suggests that these responses may bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 78 publications
1
85
0
2
Order By: Relevance
“…It is suggested that in these combined heart-lung and heartkidney transplants, the lung and renal system become the primary regions of interface between recipient and host immune systems; hence, graft coronary vasculature is relatively less affected [26,38,39]. Immunologic mechanisms that regulate CAV are complex and heterogeneous and involve cellular and humoral aspects of adaptive and innate immune response pathways [7,9,19,[35][36][37][40][41][42].…”
Section: Immunobiology and Pathogenesis Of Coronary Allograft Vasculomentioning
confidence: 99%
See 4 more Smart Citations
“…It is suggested that in these combined heart-lung and heartkidney transplants, the lung and renal system become the primary regions of interface between recipient and host immune systems; hence, graft coronary vasculature is relatively less affected [26,38,39]. Immunologic mechanisms that regulate CAV are complex and heterogeneous and involve cellular and humoral aspects of adaptive and innate immune response pathways [7,9,19,[35][36][37][40][41][42].…”
Section: Immunobiology and Pathogenesis Of Coronary Allograft Vasculomentioning
confidence: 99%
“…Immune response is further propagated by recruitment of macrophages and other pro-inflammatory cells on to the vessel wall. Activated macrophages elaborate cytokine production and growth factor secretion [9,60,61]. Intercellular communication and coordination between infiltrating cells, adhesion molecules, endothelium, and various components of the extracellular matrix are required for successful recruitment and transmigration of leukocytes.…”
Section: Immunobiology and Pathogenesis Of Coronary Allograft Vasculomentioning
confidence: 99%
See 3 more Smart Citations